Metabolism and Excretion of Nirmatrelvir in Humans Using Quantitative Fluorine Nuclear Magnetic Resonance Spectroscopy: A Novel Approach for Accelerating Drug Development. Issue 6 (29th June 2022) - Singh, Ravi Shankar P.; Walker, Gregory S.; Kadar, Eugene P.; Cox, Loretta M.; Eng, Heather; Sharma, Raman; Bergman, Arthur J.; Van Eyck, Lien; Hackman, Frances; Toussi, Sima S.; Kalgutkar, Amit S.; Obach, R. Scott
Abstract : Typically human absorption, distribution, metabolism, and excretion (ADME) studies are executed using radiolabeled (e.g., carbon‐14) material, the synthesis of which is a time‐consuming activity. In this study, we were able to assess the metabolism and excretion of unlabeled nirmatrelvir (PF‐07321332) within the first‐in‐human study via a novel application of quantitative fluorine ( 19 F) nuclear magnetic resonance (NMR) spectroscopy in place of a standard radiolabel ADME study. Six healthy participants received a single 300‐mg oral dose of nirmatrelvir (in combination with ritonavir), and excreta were collected up to 10 days. Virtually all drug‐related material was recovered within 5 days, and mass balance was achieved with 84.9 ± 8.9% (range = 70.7–95.5%) of the administered dose recovered in urine and feces. The excretion of fluorine‐containing material in urine and feces was 47.0% and 33.7%, respectively. Unchanged nirmatrelvir represented 82.5% of the normalized drug‐related material with a carboxylic acid metabolite M5, derived from hydrolysis of the P2 amide bond, present at 12.1% of dose. Nirmatrelvir was the only drug‐related entity observed in plasma. Approximately 4.2% of the dose was excreted as metabolite M8 (measured by liquid chromatography–mass spectrometry), which was 19 F NMR silent due to hydrolysis of the trifluoroacetamide moiety. Hydrolysis of nirmatrelvir to M5 and M8 was shown to occur in cultures of human gut microflora. This successful demonstration of quantitative 19 F NMR spectroscopy to establish the mass‐balance, excretion, and metabolic profile of nirmatrelvir offers an advantageous means to execute human ADME studies for fluorine‐containing compounds early in drug development.